2013
DOI: 10.4209/aaqr.2012.08.0206
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation and Chemical Characteristics of Atmospheric Aerosol Particles and Their Source Fingerprints at Xiamen Bay

Abstract: This study investigated the diurnal variation of mass concentration and chemical composition of atmospheric aerosol particles sampled at Xiamen Bay, located on the west bank of the Taiwan Strait. Atmospheric PM 10 samples were collected at ten particulate matter (PM) sampling sites at Xiamen Bay, including five sites at the Kinmen Islands and five sites in urban Xiamen, at both daytime and nighttime during the regular and intensive sampling periods. Regular sampling was conducted to collect PM 10 with high-vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…Fig. 5 presents the diagrams of the daytime and nighttime wind roses, showing the seasonal changes of the prevailing wind direction and wind speed at the study site (Li et al, 2013). These diagrams indicate that at our study site, the prevailing winds are the southwesterly (from the South China Sea and tropical oceans) in the spring and summer and the northeasterly (from the Asian continent) in the fall and spring (Li et al, 2013).…”
Section: 2mentioning
confidence: 94%
“…Fig. 5 presents the diagrams of the daytime and nighttime wind roses, showing the seasonal changes of the prevailing wind direction and wind speed at the study site (Li et al, 2013). These diagrams indicate that at our study site, the prevailing winds are the southwesterly (from the South China Sea and tropical oceans) in the spring and summer and the northeasterly (from the Asian continent) in the fall and spring (Li et al, 2013).…”
Section: 2mentioning
confidence: 94%
“…Biomass-burning aerosols were predominantly fine particles (PM 2.5 ), which constitute a high proportion of PM 10 concentration. The PM 2.5 /PM 10 ratio at Xiamen Bay in China (Li et al, 2013), Thailand (Oanh et al, 2011), Korea (Ryu et al, 2007), and central Taiwan (Cheng et al, 2009) were found to be as high as 90, 79, 90 and 80%, respectively. Note that these findings are close to the simulated results in this study.…”
Section: Biomass-burning Aerosols and Radiative Forcingsmentioning
confidence: 99%
“…Since the detailed descriptions of CMB receptor model (e.g., CMB 8.0) are available elsewhere, only a brief summary is presented as supplementary file S1-1 and Table S-3. Ten major local source profiles (noted by * in Table S-3) obtained from previous studies were selected to conduct the source apportionment of PM 10 in this study (Li et al, 2013b). These sources surrounding the Xiamen Bay included stone processing, cement industries, ceramic plants, tile industries, coal burning, coal ash, fugitive dusts, biomass burning, construction dusts, and road dusts as shown in Table S-3.…”
Section: Chemical Mass Balanced (Cmb) Receptor Modelmentioning
confidence: 99%